Are they listening to us? A comparison of student responses to traditional vs. user-generated marketing content - Hagedorn, Mandy, author; Hallahan, Kirk, advisor; Champ, Joseph, committee member; Oldham, Kyle, committee member (Colorado State University. Libraries, 2013)
Marketers for university housing departments use a variety of traditional and digital tools to promote positive attitudes and interest among prospective student residents. This study used one-on-one semi-structured qualitative in-depth interviews to explore perceptions and reactions of ten first-year students at Colorado State University. Students were shown two examples of traditional marketer-generated content, including a printed Housing Guide publication that all admitted first-year students receive by mail and a video on Housing & Dining Services' website that features a student-guided tour of one of the residence halls on campus. Participants also reviewed a user-generated YouTube video featuring the same residence hall and the CSU Rams Class of 2017 Facebook group page that includes 3,000+ members. Marketer-generated materials resulted in positive attitudes and a greater sense of credibility, while the user-generated video and Facebook group page were not considered credible by as many of the participants. While students were not averse to using user-generated content online to form opinions and make decisions, they displayed more hesitation at trusting information found online versus information shared within their networks of peers or personal contacts. The results suggest that university-produced materials, particularly the housing department's comprehensive printed publication, continue to play a vital role in a university's promotional efforts, despite the widespread contention that students prefer to obtain information online and rely heavily on user-generated content. The study provides seven recommendations for future marketing efforts based on the students' preferences.